2009
DOI: 10.1038/nsmb.1729
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of both steps of Saccharomyces cerevisiae splicing with purified spliceosomal components

Abstract: The spliceosome is a ribonucleoprotein machine that removes introns from pre-mRNA in a two-step reaction. To investigate the catalytic steps of splicing, we established an in vitro splicing complementation system. Spliceosomes stalled before step 1 of this process were purified to near-homogeneity from a temperature-sensitive mutant of the RNA helicase Prp2, compositionally defined, and shown to catalyze efficient step 1 when supplemented with recombinant Prp2, Spp2 and Cwc25, thereby demonstrating that Cwc25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
338
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 167 publications
(362 citation statements)
references
References 37 publications
12
338
0
3
Order By: Relevance
“…In this extract, yeast B act∆prp2 spliceosomal complexes were assembled and purified as described in ref. 28 on site-specifically 32 P-labeled pre-mRNA. The pre-mRNA was produced by DNA splint-directed RNA ligation 74 of RNA fragments obtained by sitespecific DNA enzyme cleavage 75 of in vitro-transcribed actin pre-mRNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this extract, yeast B act∆prp2 spliceosomal complexes were assembled and purified as described in ref. 28 on site-specifically 32 P-labeled pre-mRNA. The pre-mRNA was produced by DNA splint-directed RNA ligation 74 of RNA fragments obtained by sitespecific DNA enzyme cleavage 75 of in vitro-transcribed actin pre-mRNA.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, we generated a yeast strain carrying the prp2-1 mutation as well as a C-terminally tandem affinity purification (TAP)-tagged version of Snu17p. The prp2-1 mutation allows purification of B act∆prp2 complexes assembled on actin pre-mRNA 28 . Previous studies have indicated that the RES complex contacts U2 snRNP proteins 4,12 , suggesting that it might bind to the pre-mRNA in the vicinity of U2.…”
Section: Npg a R T I C L E Smentioning
confidence: 99%
“…In addition, the GTPase Snu114, which together with Brr2 is associated with the U5 snRNP, is also required for the activation step and is thought to regulate Brr2 activity (Small et al 2006). The transition from the B to the B act complex involves a significant change in the spliceosome's protein composition, with numerous polypeptides such as the U1 and U4/U6 proteins being displaced, while ;20 others, including those of the NTC (nineteen complex) are stably recruited to the B act complex (Chan et al 2003;Fabrizio et al 2009;Warkocki et al 2009). For catalytic activation of the spliceosome, the DEAH-box helicase Prp2 binds together with a cofactor, Spp2, and restructures the B act complex in an ATP-dependent manner, yielding the B* complex (Roy et al 1995;Silverman et al 2004); this leads to, among other things, destabilization and/or disruption of the binding of several spliceosomal proteins (Warkocki et al 2009;Lardelli et al 2010;Ohrt et al 2012).…”
mentioning
confidence: 99%
“…The transition from the B to the B act complex involves a significant change in the spliceosome's protein composition, with numerous polypeptides such as the U1 and U4/U6 proteins being displaced, while ;20 others, including those of the NTC (nineteen complex) are stably recruited to the B act complex (Chan et al 2003;Fabrizio et al 2009;Warkocki et al 2009). For catalytic activation of the spliceosome, the DEAH-box helicase Prp2 binds together with a cofactor, Spp2, and restructures the B act complex in an ATP-dependent manner, yielding the B* complex (Roy et al 1995;Silverman et al 2004); this leads to, among other things, destabilization and/or disruption of the binding of several spliceosomal proteins (Warkocki et al 2009;Lardelli et al 2010;Ohrt et al 2012). Upon recruitment of the step 1 factor Cwc25 to the B* complex, step 1 catalysis occurs, whereby the adenosine at the BS attacks the 59 SS, generating the cleaved exon 1 and intron-lariat (IL)-39 exon intermediates (Chiu et al 2009;Warkocki et al 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation